In Vitro Culture of Ovules and Embryos from Seedless Grapes (Vitis vinifera L.) - Burger, P.; Goussard, P.G. (South African Journal of Enology and Viticulture, 2017)
Ovules of stenospermocarpic seedless grapes were cultured under different conditions. The number of embryos was not significantly increased when ovules of Muscat Seedless were cultured on a medium supplemented with the plant growth regulators indole-3-acetic acid and gibberellic acid compared to the basal medium. No correlation was found between the ovule size of Sultanina and the presence of embryos. Comparable percentages of embryos were found in small, medium and large ovules following weekly culture from four to 10 weeks after bloom. Varying results were obtained when ovules of four open-pollinated seedless cultivars were cultured on two basal media with or without activated charcoal. In all four cultivars the highest number of embryos was found at the later culture date. With three cultivars the best results were obtained when ovules were cultured on the medium of Bouquet & Davis (1989), supplemented with activated charcoal. Isolated embryos of Muscat Seedless and Sunred Seedless were cultured under various conditions and it was found that the absence of growth regulators resulted in the highest number of plantlets with normal leaves.